Power and prowess the origins of Brooke kingship in Sarawak - Walker, J. H. (John Henry) 1958- (Southeast Asia publications series, 2002)
A significant reinterpretation of Sarawak history, Power and Prowess explores the network of power, economic and ritual relationships that developed on the northwest coast of Borneo in the mid-nineteenth century, from which a coalition led by James Brooke established the state of Sarawak." "Drawing on conceptual frameworks from political science, as well as recent southeast Asian historiography, Power and Prowess offers a detailed political history of the period and new interpretations of Brooke's career. This study also retrieves from the historical sources previously concealed narratives which reflect the interests, priorities and activities of Sarawak people themselves."--Jacket